Market Religion and Religion Marketplace in Digital World - Adzkiyah Mubarokah (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. This article discusses the marketing of religion and how religion is marketed in the digital world. This research uses a descriptive qualitative approach with a library research method to This article discusses the marketing of religion and how religion is marketed in the digital world. This research uses a descriptive qualitative approach with a library research method to find out about the development of the religious market and how it is marketed in society. The study found that Religion is a product subject to the desires and changes of an unregulated market where the benefits to suppliers are high and the barriers to entry are low, there will be considerable competition for consumers. The current development of the times follows the current development of digital information technology. In the past, when religious marketing was still carried out through cultural integration, for example the spread of religion through the spread of religion by Wali Songo through puppet art, gamelan and other appropriate local activities, then developed again through the realm of education, print media and finally spread through electronic media radio, television and the internet which included the realm of developing the digital religious marketing mix. Abstrak. Artikel ini membahas tentang pemasaran agama dsn bagaimana agama itu di pasarkan di dunia digital. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi pustaka (library research) untuk mengetahui tentang perkembangan pasar agama dan bagaimana agama itu dipasarkan di masyarakat. Kajian ini menemukan hasil, bahwa Agama adalah produk yang tunduk pada keinginan dan perubahan pasar yang tidak diatur dimana manfaat bagi pemasok tinggi dan hambatan masuk rendah, akan ada persaingan yang cukup besar untuk konsumen religious. Arus perkembangan zaman mengikuti arus perkembangan teknologi informasi digital. Dahulu saat pemasaran agama masih dilaksanakan melalui pembauran budaya contoh di Indonesia misalnya penyebaran agama melalui penyebaran agama oleh Wali Songo melalui seni wayang, gamelan dan kearafin lokal yang sesuai lainnya, kemudian berkembang lagi melalui ranah Pendidikan, media cetak dan akhirnya tersebar melalui media elektronik radio, televisi dan internet yang termasuk kepada ranah perkembangan bauran pemasaran agama secara digital.